Acute and Subchronic Oral Toxicity Evaluation of Aqueous Root Extract of Dicoma anomala Sond. in Wistar Rats. (13th April 2016) - Balogun, Fatai Oladunni; Tom Ashafa, Anofi Omotayo
Abstract : The present study evaluated the safety of aqueous root extract of Dicoma anomala (AQRED) through acute and subchronic toxicity studies. Single oral dose of AQRED at the concentration of 0, 5, 300, and 2000 mg/kg as well as 125, 250, and 500 mg/kg/day was administered to rats for 14-day acute and 90-day subchronic oral toxicity studies. The results revealed no mortalities or observed clinical signs of toxicity in all the rats during both investigation periods. In subchronic toxicity testing, administration of AQRED also did not cause any changes in body weight as well as food and water consumption patterns. The haematological parameters and blood chemistry revealed no significant difference (p > 0.05 ) between the treatment and the control except in platelet count, alkaline phosphatase, and sodium levels where there was a significant increase (p < 0.05 ), although there was also a significant reduction (p < 0.05 ) in alanine transaminase, aspartate transaminase, and creatinine when compared to control. However, these changes were not reflecting the results from histology. Conclusively, the obtained results suggested that the LD50 of AQRED is in excess of 2000 mg/kg and its oral administration for 90 days revealed that it is unlikely to be toxic, hence, safe.